Traces of Mažuranić's Slovnica Hèrvatska in the grammar handbook Gyakorlati Ilir Nyelvtan by János Mihálovics - Jadranka Mlikota; Ana Lehocki-Samardžić; Borko Baraban (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2016)
The paper compares the grammar handbook Gyakorlati Ilir Nyelvtan (Baja, 1874, 21881) by Mihálovics with Mažuranić's Slovnica Hèrvatska (41869), as Mažuranić is mentioned in the foreword as the normative model used in the handbook. This comparison will include their terminology, purpose, structure, and normative prescription, and will determine in which cases Mihálovics follows Mažuranić’s grammar and in which he distances himself from it. Since the grammar handbook was published outside the Croatian (ethnic and linguistic) area, the paper will show to what extent the characteristics of the Croatian linguistic norm were preserved in the Hungarian part of the Danube Region in the late 19th century.